Feasibility of Intravenous Flat Panel Detector CT Angiography for Intracranial Arterial Stenosis - Jeon, J.S.; Sheen, S.H.; Hwang, G.J.; Kim, H.C.; Kwon, B.J. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: IV FDCT angiography is an emerging technology for the detection of intracranial vascular disease. This study was conducted to determine the feasibility of IV FDCT in estimating major atherosclerotic intracranial arterial stenosis with DSA as the reference. MATERIALS AND METHODS: DSA and IV FDCT were performed simultaneously in patients with transient ischemic attack or acute cerebral infarction. The degree and length of stenosis were measured. The stenotic vessels were categorized into 4 groups by the grade of stenosis: normal (<30%), mild (30%–49%), moderate (50%–69%), or severe (>70%). The vessels of the normal group were excluded from analysis to reduce spectrum bias. Measurement of vessels was recorded by using an electric ruler by a qualified endovascular neurosurgeon and a neuroradiologist. RESULTS: Eight hundred forty-two vessel segments in 69 patients were calculated. Mild (n = 56), moderate (n = 47) and severe stenosis (n = 46) groups were analyzed. IV FDCT had a sensitivity of 97.6%, specificity of 96.9%, and negative predictive value of 96.9% for detecting ≥50% stenosis and respective values of 91.9%, 98.2%, and 97.4% for depicting ≥70% stenosis. The difference of stenotic length between the 2 tests was not significant as an increase in the severity of stenosis (Spearman rank correlation test; r = −0.12, P = .13). CONCLUSIONS: IV FDCT can be a feasible alternative as a noninvasive method for evaluating stenosis of the major intracranial arteries. A1segment of the anterior cerebral arteryCIconfidence intervalFDCTflat panel detector CTM1 or M2segments of the middle cerebral arteryP1segment of the posterior cerebral arteryV4segment of the vertebral artery